Universo histórico-conceitual do turismo e interdisciplinaridade: reileituras de práticas docentes na formação superior em turismo - Marinho, Marcela Ferreira (My University, 2020)
The problem question of the present investigation is: The appropriation of the historical-conceptual universe of tourism associated with the reflection on concepts of interdisciplinarity and respective practice and the experience, by professors of graduation in Tourism, of a pedagogical dynamics guided by a contemporary and epistemological approach through a relational pedagogical matrix, do they contribute to rethinking interdisciplinary relations between tourism and other areas of knowledge that establish an interface with it, resulting in reflective movements towards the rereading of pedagogical practices developed in these courses? This investigation aims to contribute to the construction of subsidies of an epistemological-pedagogical nature involving the historical-conceptual universe of tourism, in order to favor the rethinking of the pedagogical practice of / by teachers from other areas working in undergraduate courses in Tourism. Theoretical support for reflections is guided by the relationship between Tourism - its historical perspective and its theoretical-epistemological approach - and Interdisciplinarity - early historical movements and the development of scientific thought. As the core of the methodological modus operandi of the research, the corpus of the theoretical framework was elaborated based on the epistemology of Gaston Bachelard - scientific pedagogy - and on the psychopedagogical approach of Lev Vygotsky - sociointeractionist relations -, as a fundamental part to identify the direction of the study, possible gaps or aspects that deserve more attention. The investigation was an essayistic nature, qualitative and of an exploratory-experimental level, in order to establish possible theoretical-methodological interfaces between the approaches of Bachelardian scientific pedagogy and Vygotsky's sociointeractionist pedagogy, in the analysis of the problem-issue. This methodological approach enabled the construction of a qualitative exploratory test, as a pilot workshop held in Portugal, whose critical procedural and results analysis provided subsidies for the planning and implementation of the target workshop held in Brazil, in order to assess the reflective movements developed by teachers, through the researcher's mediation, in the direction of building relationships between their areas of knowledge and tourism. Although they occurred differently for each subject, it was observed, in the interactions promoted by the researcher, not only relationships established procedurally by teachers in their experiences (psychopedagogical) and experiences (epistemological, via scientific pedagogy), fostered by the workshop sessions, but also movements to overcome the epistemological obstacles that happen in different times, ways and forms for each teacher. This meant enabling a space that facilitates interaction, listening and speech: a space of opening for the Other, a space of hospitality established in the dynamics of welcoming, which generates changes and cognitive, affective and relational learning: space, metaphorically, called scientific hospitality. We highlight the recognition of interdisciplinarity in this process, and the reiteration of the possible contribution of the professor of each area in the formation of the subject of Tourism and the professional of Tourism. On the other hand, it leaves a mark on the clarity it has about the inevitable possibility of re-reading (rethinking) the pedagogical practice based on what was developed in the workshop.
A questão-problema da presente investigação é: Apropriação do universo históricoconceitual do turismo associada à reflexão sobre conceitos de interdisciplinaridade e respectiva prática e à vivência, por docentes de graduação em Turismo, de uma dinâmica pedagógica balizada por uma abordagem epistemológica contemporânea e por uma matriz pedagógica relacional, contribuem no repensar de relações interdisciplinares entre Turismo e outras áreas de conhecimento que com ele estabelecem interface, disso derivando movimentos reflexivos no sentido de releituras de práticas pedagógicas desenvolvidas nesses cursos? Esta investigação visa contribuir com a construção de subsídios de cunho epistemológico-pedagógico envolvendo o universo histórico-conceitual do turismo, no sentido de favorecer o repensar da prática pedagógica de/por docentes de outras áreas atuando em cursos de graduação em Turismo. O suporte teórico para as reflexões é balizado pelas relações entre Turismo – sua perspectiva histórica e sua abordagem teóricoepistemológica – e Interdisciplinaridade – movimentos históricos iniciais e desenvolvimento do pensamento científico. Como cerne do modus operandi metodológico da pesquisa, elaborou-se o corpus do referencial teórico com base na epistemologia de Gaston Bachelard – pedagogia científica – e na abordagem psicopedagógica de Lev Vygotsky – relações sociointeracionistas –, como parte fundamental para identificar os rumos do estudo, suas possíveis lacunas ou aspectos que mereceriam maior atenção. A investigação foi de natureza ensaística, qualitativa e de nível exploratório-experimental, com o intuito de estabelecer possíveis interfaces teórico-metodológicas entre as abordagens da pedagogia científica bachelardiana e da pedagogia sociointeracionista de Vygotsky, na análise da questão-problema. Essa abordagem metodológica possibilitou construção de teste exploratório qualitativo, como oficina-piloto realizada em Portugal, cuja análise crítica processual e de resultados propiciou subsídios para o planejamento e implementação da oficina-alvo realizada no Brasil, com o intuito de avaliar os movimentos reflexivos desenvolvidos pelos docentes, via mediação da pesquisadora, na direção de construções de relações entre suas áreas de conhecimento e o Turismo. Embora tenham ocorrido diferentemente para cada sujeito, observaram-se, nas interações promovidas pela pesquisadora, não só relações estabelecidas processualmente pelos professores em suas vivências (psicopedagógicas) e experiências (epistemológicas, via pedagogia científica), fomentadas pelas sessões da oficina, como também movimentos de superação dos obstáculos epistemológicos que acontecem em tempos, modos e formas diferentes para cada professor. Isso significou possibilitar um espaço facilitador de interação, de escuta e de fala: um espaço de abertura para o Outro, espaço de hospitalidade instituído na dinâmica do acolhimento, gerador de modificações e de aprendizagens cognitivas, afetivas e relacionais: espaço, metaforicamente, denominado de hospitalidade científica. Destaca-se o reconhecimento da interdisciplinaridade nesse processo, e a reiteração da possível contribuição do docente de cada área na formação do sujeito do Turismo, do profissional do Turismo. De outra parte, deixa marcada a clareza que tem sobre a inevitável possibilidade de releitura (repensar) da prática pedagógica a partir do que fora desenvolvido na oficina.
Keywords: Turismo - Estudo e ensino (Superior); Ensino superior; Abordagem interdisciplinar do conhecimento na educação; Hospitalidade; Tourism - Study and teaching (Higher); Education, Higher; Interdisciplinary approach in education; Hospitality